Catalysis seen in action - Tromp, Moniek (Philosophical transactions of the Royal Society of London. Series A: Mathematical, physical, and engineering sciences, 2015)
Synchrotron radiation techniques are widely applied in materials research and heterogeneous catalysis. In homogeneous catalysis, its use so far is rather limited despite its high potential. Here, insights in the strengths and limitations of X-ray spectroscopy technique in the field of homogeneous catalysis are given, including new technique developments. A relevant homogeneous catalyst, used in the industrially important selective oligomerization of ethene, is taken as a worked-out example. Emphasis is placed on time-resolved operando X-ray absorption spectroscopy with outlooks to novel high energy resolution and emission techniques. All experiments described have been or can be done at the Diamond Light Source Ltd (Didcot, UK).